Diseño e implementación de un prototipo generador de electricidad mediante el efecto termoeléctrico con el uso de celdas peltier - Casa Casa, Ricardo Ignacio (2019)
This project contains educational aspects such as research, technological development and innovation, it is aimed at gathering technical information on the use of alternative and renewable energies to promote the efficient use of energy. The geographic location of our country and the operating characteristics of the Peltier cells allow us to take advantage of the geothermal energy existing in the thermal waters and thus to apply them in a system of electric power generation. The knowledge and skills acquired in the course of university life allow the design of an energy generating system based on the principles of thermodynamics, heat transfer, electrical circuits, to finally achieve the construction and implementation of a prototype generator of electricity through the thermoelectric effect with the use of Peltier cells, and to determine the efficiency that the implementation of these devices will have in environmental situations of constant changes.